Palatal Schwannoma: An Analysis of 45 Literature Reports and of an Illustrative Case - Dokania,Vivek (2019)
Abstract Introduction Schwannomas are benign tumors originating from differentiated Schwann cells. Being the least common intraoral neoplasm of neural origin, it is rarely seen in the palate. The literature lacks an extensive review of intraoral schwannoma confined to the palate. Objective To review previously reported cases of palatal schwannoma along with an illustrative case, and to provide a better insight regarding clinicopathological and radiological features of this neural tumor in a rare intraoral site. Data Synthesis We present a case of palatal schwannoma in a 16-year-old female. An additional 45 cases were identified in 2 medical database searches (PubMed and Google Scholar) published fromthe year 1985 onwards, and from13 countries, in the 5 continents. The ages of the patients ranged from3 to 84 years old. Palatal schwannoma showed a slight predilection to females, with a male/female ratio of ~ 1:1.81. Hard palate involvement is almost twice greater than soft palate involvement. Surgical excision was employed inalmost all of the cases, and recurrence was reported only once. Conclusion Palatal schwannomas, although rare, have been reported both over the hard and the soft palate. They mostly present as a painless, firm, well-encapsulated, slow-growing solitary lesion over the lateral palatal aspect. Imaging can add to suspicion and can delineate a differential diagnosis, but the diagnosis is confirmed by pathological examination. Fine-needle aspiration cytology (FNAC) is almost always inconclusive. Immunohistochemistry can assist in confirming a diagnosis, but is more important to rule out close differentials. Complete surgical excision is the treatment of choice, and recurrence or malignant transformation are extremely rare.